Energy efficiency mechanisms using mobile node in wireless sensor networks - Mantoro, Teddy; Ayu, Media Anugerah; Ali, Haroon Shoukat; Usino, Wendi; Kadhum, Mohammed M. (SpringerLink, 2012)
A traditional network consists of gateway sensors which transmit data to the base stations. These nodes are considered bottlenecks in multihop-networks as they transmit their data as well as data from other nodes and hence they deplete faster in energy. One way to optimize energy efficiency in a WSN is to deploy a mobile base station which could collect data without a need for gateway nodes, and hence the multihop bottleneck would be minimized. We compare these two variations of WSN, one consisting of the multihop approach with gateway nodes, and we propose the other network structure, whereby a mobile base station collects data individually from each node using double Fermat’s spiral model.